The Linkage Between Labour Standards and International Trade: How to Offset the Global Inequality? - Tyc, Aneta (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
From a historical point of view, the linkage between core labour standards and global trade has been recurrent for 200 years. Supporters of such a correlation argue that countries that do not respect the International Labour Organization (ILO) core labour standards gain competitive advantage that can result in a ‘race to the bottom’ phenomenon. Critics claim that protectionism and false humanitarianism is hidden behind this concept. Despite a long debate on this subject, there is still significant divergence in power between developed and developing countries. A response to the plight of many workers is still needed. Thus, the author will focus on some attempts to resolve existing problems, mainly: whether labour standards should be left to the ILO, included in the World Trade Organization (WTO) agenda or both forces should be combined; whether the inclusion of a social clause in trade agreements could improve the situation of workers; whether the imposition of trade sanctions on countries that do not adhere to the core labour standards could ensure the extension of fundamental rights of workers on their citizens. The author will also comment on the concept of a global labour and trade framework agreement (GLTFA), that is, the proposal based on international framework agreements and ILO tripartite system.
Keywords: global trade; labour standards; the ILO; the WTO